CURCUMIN IN ORAL MUCOSAL LESIONS: AN UPDATE - Rai, Arpita; Kumar, Ansul; Hasan, Shamimul; Saeed, Shazina (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The phytopharmaceutical curcumin - the Indian golden spice has been widely researched for its pharmaceutical properties. It exhibits a big promise as a therapeutic agent due to its properties such as antioxidant, analgesic, anti-inflammatory, antiseptic activity, anticarcinogenic activity, chemopreventive, chemotherapeutic activity, antitumor, antiviral, antibacterial, and antifungal and is currently in human trials for a variety of conditions. The applications of curcumin in dentistry include its use as pit and fissure sealant, dental plaque detection system, subgingival irrigant, and intracanal medicament. The aim of the present paper is to review the current literature for the use of curcumin in oral mucosal lesions. A thorough review of the existing literature encompassing PubMed, Ovid, Embase, and Google scholar was made using the keywords curcumin, turmeric, oral, mucosal, oral submucous fibrosis (OSMF), oral lichen planus (OLP), aphthous, recurrent aphthous stomatitis (RAS), leukoplakia, mucositis, reverse smoking, tobacco-associated lesions, and premalignant. No filters in relation to language or publication year were used and only in vivo studies on humans were selected. Reference lists of retrieved journal articles were searched for publications missed during the primary search. Finally, the Google search engine was used to do a comprehensive search of the World Wide Web to ensure completeness of the search. The review of the literature revealed evidence of the use of curcumin in tobacco-associated conditions of the oral cavity-OSMF, oral leukoplakia, oral lesions associated with reverse smoking and ulcerative conditions of the oral cavity- OLP, RAS, and oral mucositis has been studied. Curcumin provides the basis for a simple, safe, acceptable, and cost-effective intervention for oral mucosal disorders.